2021
DOI: 10.3390/su13052754
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Social Entrepreneurship: A Systematic Review and Meta-Analysis

Abstract: All social entrepreneurship experts state that the issue of definition is the main problem affecting research in this field. Although there is no single definition, this is clearly a new domain in the field of research on entrepreneurship. The main objective of this study is to further knowledge in this area by means of a systematic review of scientific literature to determine the conceptual development of social entrepreneurship and to identify the most interesting research trends. This study uses a research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 63 publications
0
35
0
1
Order By: Relevance
“…This aspect of the social context was an argument for García-Jurado et al The authors analyzed the entrepreneurial field, considered to be an emerging field, under the influence of the millennial generation, much more connected to technological progress. The authors found that this influence takes on the appearance of a phenomenon over the millennia and a growth factor of entrepreneurial intent [39].…”
Section: Theories Of Entrepreneurial Intentionsmentioning
confidence: 99%
“…This aspect of the social context was an argument for García-Jurado et al The authors analyzed the entrepreneurial field, considered to be an emerging field, under the influence of the millennial generation, much more connected to technological progress. The authors found that this influence takes on the appearance of a phenomenon over the millennia and a growth factor of entrepreneurial intent [39].…”
Section: Theories Of Entrepreneurial Intentionsmentioning
confidence: 99%
“…The United Kingdom defines social ventures as organizations or entities that seek the financial return of investors for the realization of social objectives or the resolution of social problems, regardless of their legal form. On the other hand, the United States defines social ventures as business ventures that promote social values through operations based on social objectives, economic principles, and innovation to alleviate or reduce social problems or market failures [11,12].…”
Section: The Social Venture Conceptmentioning
confidence: 99%
“…The concepts of social innovation and social enterprises are contested in research as well as in political life [24][25][26][27]. Social innovation is often defined as new ideas, products, services, and methods that meet social challenges.…”
Section: Social Innovation and Social Enterprise-concepts And Policy Areamentioning
confidence: 99%
“…Social innovation is often defined as new ideas, products, services, and methods that meet social challenges. These can be climate issues, integration, unemployment, an aging population, and social exclusion [27], or a more developed definition such as: a novel solution to a social problem that is more effective, efficient, sustainable, or just than existing solutions and for which the value created accrues primarily to society as a whole rather than private individuals. A social innovation can be a product, production process, or technology (much like innovation in general), but it can also be a principle, an idea, a piece of legislation, a social movement, an intervention, or some combination of them (p. 36, [28]).…”
Section: Social Innovation and Social Enterprise-concepts And Policy Areamentioning
confidence: 99%